Adrenocortical Activity and Aggressive Behavior in Children: A Longitudinal Study on Risk and Protective Effects - Bender, Doris; Lösel, Friedrich (Frontiers in Psychology, 2021)
Most research on aggression and delinquency concentrates on risk factors. There has been less attention for protective factors and mechanisms, in particular with regard to biosocial influences. Based on theories of autonomous arousal and stress reactance the present study addresses the influence of adrenocortical activity as a risk and/or protective factor in the development of antisocial behavior in children. We also investigated interactions with anxiousness and family stressors. In a prospective longitudinal study of 150 German boys, the first measurement took place at preschool age and contained an assessment of cortisol after waking up and 30 minutes later. Aggressiveness and anxiousness of the children were assessed by the kindergarten teachers with the Social Behavior Questionnaire. After six years, the children’s behavior was rated by the school teachers in middle school. Variable-oriented data analyses revealed a significant correlation between the total amount of cortisol after waking up and 30 minutes later and anxiousness both cross-sectionally and longitudinally, but not with aggressiveness. A family stress index on low SES, loss of a close relative, and divorce correlated as expected with aggressiveness but neither with cortisol nor with anxiousness. Individual-oriented data analyses showed complex patterns. Children who were high in both aggressiveness and anxiousness had the highest cortisol level and those with low anxiousness and high aggressiveness the lowest. There were significant correlations between aggressiveness and anxiousness at kindergarten age and the respective behavior problems six years later. The groups with different patterns of externalizing and internalizing problems at preschool age showed significant differences in aggression six years later. Our results underline the need for complex pattern analyses on cortisol, aggression, and anxiousness in children and for a differentiated consideration of emotional reactive aggression and unemotional instrumental aggression in children.